Gambaran Tingkat Resiliensi Masyarakat Desa Sriharjo, Imogiri Pasca Banjir - Nanang Apriyanto; Dody Setyawan (Holistic Nursing and Health Science, 2020)
Introduction: The flood disaster with the impact of the isolation of the area causes psychological problems such as anxiety, sadness, anxiety, depression, and impaired adaptation. Continued psychological disorders will cause Post Traumatic Stress Disorder (PTSD). Communities need to have the resilience to be able to manage disasters well through adaptation, maintain basic functions and immediately rise again after a disaster. The purpose of this study was to see the level of resilience of the people of Sriharjo Village, Imogiri after the Flood. Methods: This research was quantitative research with a survey descriptive design. The population in this study was community of Wunut and Sompok at Sriharjo, Imogiri Village as the most affected areas with a population of 1,573. The sampling technique was purposive sampling and got a sample size of 319 respondents. The data collection technique used a CD RISC-25 questionnaire consisting of 25 statement items, using google form media and contacted via telephone.Results: The results showed that 60.2% of respondents had high resilience. Most of the respondents have a high level of resilience to the spiritual influence variable and have a low level of resilience to the positive acceptance of change, and secure relationships variable. Conclusion: Communities living in disaster-prone areas must be able to become resilient communities by maintaining spiritual influence and increasing positive acceptance of change, and secure relationships.